2021
DOI: 10.3389/fimmu.2021.684052
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Electron Irradiation Is a Potent Alternative to Gamma Irradiation for the Inactivation of (CAR-)NK-92 Cells in ATMP Manufacturing

Abstract: BackgroundWith increasing clinical use of NK-92 cells and their CAR-modified derivatives in cancer immunotherapy, there is a growing demand for efficient production processes of these “off-the-shelf” therapeutics. In order to ensure safety and prevent the occurrence of secondary tumors, (CAR-)NK-92 cell proliferation has to be inactivated before transfusion. This is commonly achieved by gamma irradiation. Recently, we showed proof of concept that low energy electron irradiation (LEEI) is a new method for NK-92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In this report, we shed new light on potential limitations to NK-92 cell-mediated serial killing and therapeutic efficacy, specifically following irradiation, a current clinical practice preceding adoptive transfer. Prior studies have investigated the effects of irradiation on NK-92 cell-mediated killing; however, these studies used shorter cytotoxicity assays with different target cells and reported that NK-92 cytotoxic capacity is mostly retained for at least 24 h following irradiation [ 22 , 42 ]. Another study, using haNK cells 24-h post irradiation saw an increase in cytotoxicity toward multiple carcinoma cell lines compared to haNK cell killing immediately post irradiation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this report, we shed new light on potential limitations to NK-92 cell-mediated serial killing and therapeutic efficacy, specifically following irradiation, a current clinical practice preceding adoptive transfer. Prior studies have investigated the effects of irradiation on NK-92 cell-mediated killing; however, these studies used shorter cytotoxicity assays with different target cells and reported that NK-92 cytotoxic capacity is mostly retained for at least 24 h following irradiation [ 22 , 42 ]. Another study, using haNK cells 24-h post irradiation saw an increase in cytotoxicity toward multiple carcinoma cell lines compared to haNK cell killing immediately post irradiation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The profound effects of irradiation on NK-92 cytotoxic capacity indicate that radiation effects extend beyond DNA damage and likely include direct damage to proteins [ 46 , 47 ]. Ionizing radiation produces radiolysis products, such as reactive oxygen species that inactivate proteome functions including those involved in killing and DNA repair [ 42 ]. Low energy electron irradiation, as an alternative to gamma irradiation, inhibits NK-92 cell proliferation while maintaining higher cytotoxic capacity and for longer periods of time and could therefore be considered for clinical applications [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For clinical application, proliferation of NK-92 cells needs to be halted prior to infusion to avoid NK-92 cell engraftment in vivo, which could lead to the development of NK cell lymphoma. Although alternative methods are being examined [ 63 ], this “inactivation” step is most commonly performed by gamma-irradiation. We confirmed that 10 Gy gamma-irradiation effectively blocks NK-92 cell proliferation and leads to a gradual decrease in cell viability down to zero over the course of 1 week, paralleling the CAR expression kinetics after mRNA electroporation.…”
Section: Discussionmentioning
confidence: 99%